Thomas Abthorpe Cooper America's premier tragedian - Smith, Geddeth (Fairleigh Dickinson Univ. Press, 1996)
Written by contemporary actor Geddeth Smith, this biography tells the story of Thomas Abthorpe Cooper, one of America's most distinguished tragedians. To the three generations of Americans who lived during the first quarter of the nineteenth century, Cooper's name carried with it an aura of shining celebrity. His name on the playbills meant long lines at the box office, and theatrical managers clamored to engage him